2022
DOI: 10.1002/1878-0261.13211
|View full text |Cite
|
Sign up to set email alerts
|

A novel AMPK activator shows therapeutic potential in hepatocellular carcinoma by suppressing HIF1α‐mediated aerobic glycolysis

Abstract: Hepatocellular carcinoma (HCC) is characterized by rapid growth, early vascular invasion, and high metastasis. Currently available US Food and Drug Administration (FDA)‐approved drugs show low therapeutic efficacy, limiting HCC treatment to chemotherapy. We designed and synthesized a novel small molecule, SCT‐1015, that allosterically activated adenosine monophosphate‐activated protein kinase (AMPK) to suppress the aerobic glycolysis in HCC. SCT‐1015 was shown to bind the AMPK α and β‐subunit interface, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…All the other genes are downregulated [28]. In particular, the activation of AMPK, SIRT1 and SIRT3 has been suggested as a preventative and therapeutic opportunity for HCC [29][30][31]. The data reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All the other genes are downregulated [28]. In particular, the activation of AMPK, SIRT1 and SIRT3 has been suggested as a preventative and therapeutic opportunity for HCC [29][30][31]. The data reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity of TME is associated with glucose metabolism. It was shown that hypoxic conditions in TME promoted HIF-1-induced glycolysis [204]. HIF-1 promotes glycolysis by upregulating hexokinase and glucose transporters, while inhibiting mitochondrial biosynthesis [204].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…It was shown that hypoxic conditions in TME promoted HIF-1-induced glycolysis [204]. HIF-1 promotes glycolysis by upregulating hexokinase and glucose transporters, while inhibiting mitochondrial biosynthesis [204]. HIF-1 stimulates pyruvate kinase 2 (PKM2) into the nucleus to drive transcription of glycolysis-related genes [205].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…In fact, some AMPK activators are now being considered as possible drugs for the treatment of metabolic disorders and cancer [ 138 ]. In HCC, a recent report suggested that AMPK activation shows therapeutic potential [ 139 ]. Still, caution is suggested since contrasting results have been reported for cancer therapy [ 140 ].…”
Section: Metabolism-based Pharmacology Approaches In Hccmentioning
confidence: 99%